MONOSACCHARIDE COMPOSITION OF RHABDOVIRUSES INFECTING ANIMALS AND PLANTS - Л. Ф. Діденко; Л. Д. Варбанець; Т. Ю. Сaбiровa; О. В. Серденко; О. С. Броварська; М. Я. Співак (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2008)
Comparative studies of plant and animal rhabdoviruses are of great importance because of their similar structural organization, morpholoical characters and functional properties of their components. Rhabdoviruses differ from plus-genome viruses, because in addition to their minus-RNA chain and multifunctional proteins, they contain also fatty acids and carbohydrates.